Chronic kidney disease and coenzyme Q10 supplementation. (2nd March 2019) - Hargreaves, Iain; Mantle, David; Milford, David
Abstract : Among the potential causes of chronic kidney disease (CKD), mitochondrial respiratory chain (MRC) dysfunction, oxidative stress and inflammation have been implicated as contributor factors to the pathogenesis of this disorder. It is thought that CoQ10 supplementation may offer some therapeutic potential in the treatment of patients with CKD, since CoQ10 has a key role in normal MRC function, as well as having antioxidant and anti-inflammatory action. This article will outline the current knowledge on the use of CoQ10 in the treatment of CKD